Perdebatan Aspek-Aspek Ketuhanan dalam Teologi Islam dan Kaitannya dengan Kalimat Tauhid (Analisis Terhadap Tiga Mazhab Besar Teologi Klasik: Mu’tazilah, Asyariyah dan Al-Maturidiyah) - Apriyani, Nur; Amri, Muh.; Aderus, Andi (Indo-MathEdu Intellectuals Journal, 2024)
This article aims to discuss the debate on the aspects of divinity in Islamic theology and its relation to the sentence of monotheism based on the madhhab Mu'tazilah, Asyariyah and Al-Maturidiyah. This study is a literature study with a qualitative approach that uses descriptive analysis. The data is taken from articles published on Google Scholar. Furthermore, a strict selection is carried out for these articles by evaluating the abstract, methodology, results, and relevance of each article. Conclusions were drawn from the findings, and the practical and theoretical implications of the study were identified. The results of the analysis show that Islamic theological schools such as Mu'tazilah, Ash'ariyah, and Maturidiyah debate various aspects of divinity in the context of monotheistic sentences. Mu'tazilah emphasizes the intellect and justice of Allah, while Ash'ariyah balances reason and revelation, rejects anthropomorphism in understanding God's attributes, and affirms God's decree and destiny. Maturidiyah, on the other hand, has a more moderate approach and emphasizes the importance of faith, and views the attributes of Allah as something that can be understood in a limited way by human reason. Despite their different approaches, these schools seek to understand and explain aspects of divinity within the framework of monotheism which is a fundamental principle in Islamic teachings